The Plant-Derived Bauhinia bauhinioides Kallikrein Proteinase Inhibitor (rBbKI) Attenuates Elastase-Induced Emphysema in Mice - Bruno Tadeu Martins-Olivera; Rafael Almeida-Reis; Osmar Aparecido Theodoro-Júnior; Leandro Vilela Oliva; Natalia Neto dos Santos Nunes; Clarice Rosa Olivo; Marlon Vilela de Brito; Carla Máximo Prado; Edna Aparecida Leick; Mílton de Arruda Martins; Maria Luiza Vilela Oliva; Renato Fraga Righetti; et al. (Mediators of Inflammation)
Background. Elastase mediates important oxidative actions during the development of chronic obstructive pulmonary disease (COPD). However, few resources for the inhibition of elastase have been investigated. Our study evaluated the ability of the recombinant plant derived Bauhinia bauhinioides Kallikrein proteinase Inhibitor (rBbKI) to modulate elastase-induced pulmonary inflammation. Methods. C57Bl/6 mice were given intratracheal elastase (ELA group) or saline (SAL group) and were treated intraperitoneally with rBbKI (ELA-rBbKI and SAL-rBbKI groups). At day 28, the following analyses were performed: (I) lung mechanics, (II) exhaled nitric oxide (ENO), (III) bronchoalveolar lavage fluid (BALF), and (IV) lung immunohistochemical staining. Results. In addition to decreasing mechanical alterations and alveolar septum disruption, rBbKI reduced the number of cells in the BALF and decreased the cellular expression of TNF-α, MMP-9, MMP-12, TIMP-1, eNOS, and iNOS in airways and alveolar walls compared with the ELA group. rBbKI decreased the volume proportion of 8-iso-PGF2α, collagen, and elastic fibers in the airways and alveolar walls compared with the ELA group. A reduction in the number of MUC-5-positive cells in the airway walls was also observed. Conclusion. rBbKI reduced elastase-induced pulmonary inflammation and extracellular matrix remodeling. rBbKI may be a potential pharmacological tool for COPD treatment.